Effects of Moderate and Vigorous Physical Exercises on Serum Liver Function Tests of Healthy Male Individuals in Anambra State - Saheed Opeyemi Usman; Jude A Onuegbu; Samuel C Meludu; Japhet M Olisekodiaka; Christian Ejike Onah; John Ndubuisi Udo; Chigozie O Ifeadike; Ifeoma Anne Modebe (International Journal of Medical Research, 2015)
Objectives: The objective of this study was to determine and compare results of the effect of moderate and vigorous exercises on AST, Alanine Aminotransferase (ALT), Alkaline Phosphatase (ALP), Gamma Glutamyl Transferase (GGT), Total Bilirubin (TBIL) and Direct Bilirubin (DBIL) before exercise, two weeks after exercise and four weeks after exercise. Methodology: Serum concentration/activity of AST, ALT, ALP, GGT, TBIL and DBIL of both vigorous exercise group (50 male individuals who played football for 2 hours daily for 5 days/week) and moderate exercise group (50 male individuals who played football for 30 minutes daily for 3 days/week) were determined using enzymatic spectrophotometric method. All data were expressed as Mean ± Standard Deviation (SD) and analyzed with Analysis of Variance (ANOVA) while multiple comparisons were done using Post Hoc test. Pearson’s correlation coefficient was used for correlational analysis. Results: In the moderate exercise group, mean BMI was reduced while ALT, AST, ALP, GGT were increased, with TBIL and DBIL altered but no significance at P<0.05 all through. In the vigorous exercise group, mean serum ALT was significantly increased at P<0.05 mainly 4 weeks after exercise as compared with results before exercise. Mean serum AST was significantly increased all through at P<0.05. However, mean BMI was decreased while mean serum ALP and GGT were increased, with mean serum TBIL and DBIL altered but not significant at P<0.05. Conclusion: Vigorous physical exercise can substantially increase fitness, but, moderate physical exercise, when performed frequently and over an extended period, produces enhanced biochemical parameters and reduced risks of cardiovascular disease.